2020
DOI: 10.1039/c9dt04732h
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of novel lithium β-diketonate glyme adducts: the effect of molecular engineering on the thermal properties

Abstract: Coordination of monoglyme and diglyme to Li ion, in addition to the anionic hexafluoro-acetylacetone, gives rise, respectively, to a polymeric network and dimeric units with challenging mass transport properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…Concluding, the present syntheses of adducts 2 , 3 , and 4 give us a good understanding of the polyether chain’s effect on the central metal β-diketonate structure’s coordination chemistry. Analogous coordination behavior has recently been observed for the Li and K ions using the hfa anionic ligand and the same glyme Lewis base ligands [ 43 , 44 ].…”
Section: Resultssupporting
confidence: 61%
“…Concluding, the present syntheses of adducts 2 , 3 , and 4 give us a good understanding of the polyether chain’s effect on the central metal β-diketonate structure’s coordination chemistry. Analogous coordination behavior has recently been observed for the Li and K ions using the hfa anionic ligand and the same glyme Lewis base ligands [ 43 , 44 ].…”
Section: Resultssupporting
confidence: 61%
“…[21][22][23] Former studies have shown that glymes play a crucial role in stabilizing complexes of alkaline-earth, [24][25][26][27][28] transition [29,30] and rare-earth metals [31,32] through oxygen-ion complexation. Recently, we have also devoted our attention to alkali metals, namely Li [33] and Na. [34] We have recently reported the synthesis and the crystal structures of Lithium β-diketonate complexes with a polymeric, [Li 12 [33] In regard to Na, a novel monomeric complex of the type, Na(hfa) * tetraglyme, [34] has been synthesized and applied to the sol-gel processes of NaYF 4 phase.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have also devoted our attention to alkali metals, namely Li [33] and Na. [34] We have recently reported the synthesis and the crystal structures of Lithium β-diketonate complexes with a polymeric, [Li 12 [33] In regard to Na, a novel monomeric complex of the type, Na(hfa) * tetraglyme, [34] has been synthesized and applied to the sol-gel processes of NaYF 4 phase. [35] An analogous coordination architecture for Na has been observed in the heterobinuclear Na-RE (RE = Y and Gd) complexes of formula [RE(hfa) 4 ] À [Na * tetraglyme] + .…”
Section: Introductionmentioning
confidence: 99%
“…[57][58][59][60][61] Lead β-diketonates are used as precursors in vapor phase processes, such as the case of Pb(tmhd) 2 [(H-tmhd = 2,2,6,6-tetramethyl-3,5-heptanedione)], Pb(acac) 2 , [(H-acac = 2,4-pentanedione)], and their derivatives. 56,62 It has been demonstrated that glymes, through oxygen-ion complexation, are very important for the stabilization of alkaline, 61,63,64 alkaline-earth 65,66 and rare-earth 67 metals. The presence of such a class of multidentate ligands, in fact, permits also to fine-tune the properties of the final metal adducts in terms of thermal stability, moisture-and air-sensitivity, solubility, and volatility.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that glymes, through oxygen-ion complexation, are very important for the stabilization of alkaline, 61,63,64 alkaline-earth 65,66 and rare-earth 67 metals. The presence of such a class of multidentate ligands, in fact, permits also to fine-tune the properties of the final metal adducts in terms of thermal stability, moisture- and air-sensitivity, solubility, and volatility.…”
Section: Introductionmentioning
confidence: 99%